A novel immunomodulatory treatment involving mycophenolate mofetil and corticosteroids for pediatric autoimmune cytopenias. Issue 2 (12th September 2016) - Panigrahi, Arun; Clark, Amy; Myers, John; Raj, Ashok
Abstract: Background: Successful treatment of both pediatric autoimmune hemolytic anemia (AIHA) and immune thrombocytopenic purpura (ITP), specifically those that are refractory to first‐line therapies, remains unsatisfactory in terms of long‐term remission and medication side effects. Here, we propose a novel combination therapy of mycophenolate mofetil (MMF), an adjunct immunosuppressive, and short‐term corticosteroids for the treatment of persistent or chronic autoimmune cytopenias in children. This combination may allow for rapid decrease of steroid usage as well as prolonged count stabilization with minimal toxicity to the patient. Procedure: Prospective case series of nine patients, six with persistent or chronic ITP and three with persistent or chronic AIHA, between the ages of 5 and 19 years who are being treated with combination therapy consisting of corticosteroids and MMF. Results: All patients with ITP (Patients 4–9) and AIHA (Patients 1–3) met complete response (CR) criteria, as they all initially achieved platelet counts 100 × 10 9 l –1 or more or hemoglobin level greater than or equal to 10 g/dl, respectively, while on combination therapy and then maintained this level or higher while on MMF alone after steroids were discontinued. Conclusions: Our results are very promising, as MMF appears to be an effective and well‐tolerated adjunct immunosuppressant that allows for rapid weaning of steroid usage, minimal adverse side effects to the patients, and long‐term stabilization of counts, a goal that has not been achieved successfully with other secondary treatment modalities. Therefore, this novel combination therapy may be an excellent alternative for the treatment of persistent or chronic autoimmune cytopenias in the pediatric population.